THE ROLE OF CORPORATE GOVERNANCE IN STOCK MARKET VALUATION: A STUDY (International Journal of Food and Nutritional Sciences, 2022)
This paper seeks to study the role of corporate governance in influencing stockmarket valuation. Corporate governance encompasses the mechanisms and principles bywhich companies are directed and controlled, aiming to ensure accountability, transparency,and fairness in their operations. Effective corporate governance is closely linked to higherstock market valuations for several reasons. Firstly, transparent financial reporting practicesprovide investors with accurate and timely information about a company's financial healthand performance. This transparency reduces information asymmetry and enhances investortrust, thereby potentially increasing stock prices. Secondly, the composition andindependence of a company's board of directors play a pivotal role in governance. Boardswith a majority of independent directors are better positioned to oversee managementdecisions objectively and in the best interests of shareholders. This oversight fostersconfidence among investors that the company is being governed responsibly, which canpositively impact its market valuation. Additionally, executive compensation structures thatalign with long-term shareholder interests incentivize management to focus on sustainablegrowth and profitability. Companies that link executive pay to performance metrics such asearnings per share, return on equity, or total shareholder return are viewed favorably byinvestors, leading to higher stock valuations. Furthermore, the protection of minorityshareholder rights and adherence to ethical standards are crucial aspects of corporategovernance. Companies that respect shareholder rights and operate ethically are perceivedas less risky and more attractive investments. This perception can lead to increased demandfor their shares in the market and, consequently, higher stock prices.